Issues of EU member nations' shared sovereignty, institutions, and economic development - Ismatilla Mardanov (Economies, 2023)
To investigate the effects of the European Union's (EU) member nations' shared sovereignty on economic growth. The member nations have lost substantial political and economic independence (sovereignty) and democracy. Therefore, their governments cannot facilitate rapid economic growth in their countries, affecting the EU as a whole. Data from the World Bank, institutional research entities, and the EU were utilized. The dependent variable is economic growth, and the independent and moderating variables are mainly institutions and the European Sovereignty Index. Shared sovereignty and its specific categories and foreign direct investment (FDI) outflows negatively impact economic development in the EU. Shared sovereignty negatively moderates the relationship between political rights and economic development and between FDI outflows and economic development. Democracy in member nations is formal rather than real. The present study focused on the EU's problems rather than its achievements and empirically investigated the direct and moderating effects of national sovereignty and member-country institutions on member-country economic growth. This focus and the nature of the investigation constitute the originality of the present study and reduce the gap in the literature about the effects of sovereignty, institutions, and capital spillovers (FDI outflows) on economic growth in Europe. The value of the study is in its findings, which should trigger holistic research efforts on the pros and cons of the EU for Europe, democracy, the economy, and the world.
Keywords: 330; the European Union; shared sovereignty; democracy; FDI; economic growth